Problems of Organizing a Buffer Zone of Architectural Monuments of the Uzbek Republic - Polotov К. К.; Isakov, S. S. (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article, the main problem is the preservation of the architectural appearance of the city as a single historical ensemble, and the development of recommendations, the observance of which will ensure the harmonious unity of the new building, historical and natural environment.